2022
DOI: 10.3390/nu14091686
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium-to-Calcium Ratio and Mortality from COVID-19

Abstract: Obesity, type 2 diabetes, arterial hypertension, decrease in immune response, cytokine storm, endothelial dysfunction, and arrhythmias, which are frequent in COVID-19 patients, are associated with hypomagnesemia. Given that cellular influx and efflux of magnesium and calcium involve the same transporters, we aimed to evaluate the association of serum magnesium-to-calcium ratio with mortality from severe COVID-19. The clinical and laboratory data of 1064 patients, aged 60.3 ± 15.7 years, and hospitalized by COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 37 publications
1
24
0
2
Order By: Relevance
“…Moreover, other studies reported an important role of Mg in the prognosis of patients affected by COVID-19. For example, Guerrero-Romero et al analyzed 1064 patients with COVID-19, showing a significant association between serum magnesium-calcium ratio and mortality in severe forms of the disease [ 27 ]. Similarly, a retrospective cohort study analyzing 390 hospitalized patients with COVID-19 showed that reduced kidney function and lower serum Mg levels were associated with increased mortality in obese patients affected by COVID-19 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, other studies reported an important role of Mg in the prognosis of patients affected by COVID-19. For example, Guerrero-Romero et al analyzed 1064 patients with COVID-19, showing a significant association between serum magnesium-calcium ratio and mortality in severe forms of the disease [ 27 ]. Similarly, a retrospective cohort study analyzing 390 hospitalized patients with COVID-19 showed that reduced kidney function and lower serum Mg levels were associated with increased mortality in obese patients affected by COVID-19 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some works explored the possible role of Mg in COVID-19 to predict the prognosis in these patients [ 26 , 27 , 28 , 29 , 30 ]. However, no study so far has examined the role of Mg for long COVID prediction, an increasing entity with limited therapeutical options [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…These changes decrease the activity of sulfotransferase enzyme 2B1b (SULT2B1b), as a result of which the sulfurylation of cholesterol to cholesterol sulfate is reduced. The reduction of cholesterol sulfate reduces the electrical charge of red blood cells and increases the risk of agglutination and thrombosis 42 , 43 . The low serum level of Magnesium and Na has been shown in patients who are admitted to ICU in a study from Iran 44 .…”
Section: Discussionmentioning
confidence: 99%
“…With a serum Mg/Ca ratio of 0.4, the optimal and the range from 0.36 to 0.28 was too low; the serum Mg/Ca ratio of our results of 0.21 was very low, and 49% (38 cases) of patients were below 0.20. Data from 1064 patients aged 60 years and hospitalized by COVID-19 show that an Mg/Ca ratio ≤ 0.20 is powerfully related with mortality in patients with severe COVID-19 [ 165 ]. The Mg/Ca ratio ≤ 0.20 is used as a mortality predictor in patients with CV and neoplastic illnesses [ 165 , 166 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data from 1064 patients aged 60 years and hospitalized by COVID-19 show that an Mg/Ca ratio ≤ 0.20 is powerfully related with mortality in patients with severe COVID-19 [ 165 ]. The Mg/Ca ratio ≤ 0.20 is used as a mortality predictor in patients with CV and neoplastic illnesses [ 165 , 166 ]. These results support the high risk in our series of developing chronic diseases and an increased risk of mortality.…”
Section: Discussionmentioning
confidence: 99%